Neuroendocrine differentiation markers guide treatment sequence selection in metastatic castration‐resistant prostate cancer. Issue 6 (6th January 2019) - Fan, Liancheng; Yang, Yan; Chi, Chenfei; Ma, Xiaowei; Wang, Rui; Gong, Yiming; Zheng, Hongying; Pan, Jiahua; Zhu, Yinjie; Dong, Baijun; Xue, Wei
Abstract : Background: To evaluate the value of the serum neuroendocrine differentiation (NED) markers in helping to select the best treatment sequence of abiraterone acetate (AA) and docetaxel‐prednisone (DP) in mCRPC. Methods: Eighty‐eight mCRPC patients were identified (42 in the DP‐to‐AA group and 46 in the AA‐to‐DP group). The serum levels of NED markers were measured before the first‐line treatment in 88 patients and also before and after DP therapy in 38 patients. We determined their impact on OS, radiographic progression‐free survival (rPFS), and PSA‐PFS. Results: In men with an elevation of at least one NED marker ( n  = 46) before the first‐line treatment, those who received AA and then DP had significantly better worse OS (21.7 months [95% CI 21.0‐22.4] vs 19.9 months (95% CI 15.3‐24.5); P  = 0.023. In a multivariate Cox regression analysis, treatment sequencing selection (selecting DP‐AA rather than AA‐DP) independently predicted OS (HR 0.4, 95% CI 0.2‐0.9, P  = 0.035) in patients with an elevation of at least one NED marker. However, in the subgroup without NED marker elevation, there was no significant difference in clinical outcomes between AA‐DP and DP‐AA groups (all P  > 0.05). In the group with continued NED marker evaluation during DP treatment, patients with higher baseline NED markers and obtaining PSA response to DP were more inclined to experience NED markers decline. Conclusions: Elevated pretreatment serum NED markers might indicate mCRPC patients would get better clinical outcomes from DP‐AA than AA‐DP. In contrast, those without NED marker elevation had similar outcomes regardless of which agent was chosen first. mCRPC patients with elevated NED markers and chemotherapy response were more inclined to obtain NED markers decline during DP therapy, which could account for this phenomenon.